Network games with heterogeneous players - Olena Orlova (Bielefeld University, Center for Mathematical Economics (IMW), 2021)
We consider network games in which players simultaneously form partnerships and choose actions. Players are heterogeneous with respect to their action preferences. We characterize pairwise Nash equilibria for a large class of games, including coordination and anti-coordination games, varying the strength of action preferences and the size of the linking cost. We find that, despite the symmetry and simplicity of the setting, quite irregular network structures can arise in equilibrium, implying that heterogeneity in players' action preferences may already explain a large part of observed irregularity in endogenously formed networks.
urn:nbn:de:0070-pub-29602582
Keywords: C62; C72; D85; 330; network games; strategic network formation; preference heterogeneity; efficiency